Narratologie und vormoderne japanische Literatur Theoretische Grundlagen, Forschungskritik und sprachlich bedingte Charakteristika japanischer Erzähltexte des 10. bis 14. Jahrhunderts - Balmes, Sebastian (Welten Ostasiens / Worlds of East Asia / Mondes de l'Extrême Orient, 2022)
The fundamental characteristics of Japanese narrative texts written between the tenth and the fourteenth centuries can be defined using the categories voice, perspective, and distance. This volume critically reviews existing theories to build the methodological foundation for narratological research into this literature. This theory of Japanese narrative thus makes a contribution to both narratology and Japanese studies.